Teacher Research as TESOL Professional Development: A Case Study - Margaret Kitchen; Maree Jeurissen (New Zealand Journal of Teachers' Work)
This article outlines a case study of a group of teacher-researchers who carried out individual research projects investigating aspects of second language acquisition with students in mainstream primary and secondary schools. The teachers were undertaking professional development in TESOL (Teaching English to Speakers of Other Languages). The teacher-researchers all successfully completed their projects but overcame many hurdles in order to do so. The constraints of carrying out teacher research are discussed and implications and recommendations for the provision of a healthy research culture in New Zealand schools are suggested.